Generally Accepted Accounting Principles vs. Tailored Accounting Principles in Lending Agreements: Canadian Evidence (Book). - Pastena, Victor S. (The Accounting Review, 1987)
Abstract Reviews the book " GAAP (Generally Accepted Accounting Principles) vs. TAP (Tailored Accounting Principles) in Lending Agreements: Canadian Evidence," by David B. Thornton and Murray J. Bryant.